2012
DOI: 10.1155/2012/531608
|View full text |Cite
|
Sign up to set email alerts
|

A New Bottle Design Decreases Hypoxemic Episodes during Feeding in Preterm Infants

Abstract: Oxygen saturation is lower during bottle feeding than during breastfeeding in preterm infants. Our objective was to compare two different bottle systems in healthy preterm infants before discharge in terms of SpO2 and oral feeding efficiency (rate of milk intake). Infants without supplement oxygen needs were evaluated twice on the same day during two consecutive feeds, by the same nurse. Infants served as their own controls for comparison of two systems of bottles, the order of which was randomized. The new bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Various studies focus on the influence of a specific bottle or nipple design on a particular health parameter of the infant. These studies comparing BNSs focused, inter alia, on vital parameters such as oxygen saturation during bottle-feeding with a particular feeding teat design [ 7 , 20 , 22 ] and sucking skills [ 7 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies focus on the influence of a specific bottle or nipple design on a particular health parameter of the infant. These studies comparing BNSs focused, inter alia, on vital parameters such as oxygen saturation during bottle-feeding with a particular feeding teat design [ 7 , 20 , 22 ] and sucking skills [ 7 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preterm infants have significant desaturation during bottle-feeding [ 23 ], but it could be shown that oxygen saturation increases significantly if a vented BNS is used [ 20 ]. Interestingly, some authors reported significantly lower SpO2 after feeding and attribute this to aerophagia in terms of burping and gastric distress [ 7 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] In addition, adapting the flow rate has been shown to have positive effects on sucking patterns and suck-swallowbreathe coordination. 28,29) Therefore, TFs may assist preterm infants with immature physiological functions to achieve more competent rhythmic oral feeding.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…The poor control of breathing is most evident during feeding, which requires a co-ordinated suck-swallow-breathe mechanism. There is evidence of increased apnoeic episodes during feeding in infants born preterm (Thoyre & Carlson, 2003), which may be potentiated in bottlefed babies as a result of increased vacuum with sucking (Jenik et al, 2012). In addition, increased respiratory muscle activation has been observed during feeding desaturation in preterm infants compared with term infants, indicating an increased work of breathing and thoraco-abdominal asynchrony that will be likely to contribute to respiratory fatigue (Kwon, Park, Jeong, Kim, & Lee, 2018).…”
Section: New Findingsmentioning
confidence: 99%